Early Life Stress Delays Sexual Maturation in Female Mice - Manzano Nieves, Gabriela; Schilit Nitenson, Arielle; Lee, Hye-In; Gallo, Meghan; Aguilar, Zachary; Johnsen, Angelica; Bravo, Marilyn; Bath, Kevin G. (Frontiers in Molecular Neuroscience, 2019)
In humans, some forms of early life stress (ELS) have been linked with precocious puberty, altered brain maturation, and increased risk for a variety of forms of pathology. Interestingly, not all forms of ELS have been found to equally impact these metrics of maturation. In recent work, we have found that ELS in the form of limited bedding (LB) from P4 to P11, was associated with precocious hippocampus maturation in males and increased risk for depressive-like pathology and attentional disturbance in female mice. Here, we sought to test whether ELS in the form of LB also impacted the timing of sexual maturation in female mice. To establish rate of somatic and sexual development, distinct cohorts of mice were tested for weight gain, timing of vaginal opening, and development of estrous cycling. ELS animals weighed significantly less than controls at every timepoint measured. Onset of vaginal opening was tracked from P21 – 40, and ELS was found to significantly delay the onset of vaginal opening. To test the impact of ELS on estrous cycle duration and regularity, vaginal cytology was assessed in independent groups of animals using either a continuous sampling (daily from P40 – P57) or random sampling approach (single swab at P35, P50, or P75). ELS did impact measures of estrous cycling, but these effects were dependent upon the sampling method used. We also tested the impact of ELS on anxiety-like behaviors over development and across the estrous cycle. We observed a developmental increase in anxiety-like behavior in control but not ELS mice. No effect of estrous cycle stage was found on anxiety-like behavior for either group of mice. Together these results provide evidence that ELS in the form of LB delays somatic and sexual development. Additional work will be required to determine the mechanism by which ELS impacts these measures, and if these effects are common to other models of ELS in rodents.